The effect of coring method on beef longissimus muscle shear force values - Francis, S.J.; Allen, Dell M.; Kastner, Curtis L.; de Felicio, P.E. (American Society of Animal Science, 2008)
Thirty Zebu steer carcasses were selected at Sao Paulo, Brazil commercial slaughter facility on the basis of A, C or E USDA beef carcass maturity standards. The longissimus muscle of the short loin was excised 7 days postmortem, and a 2.54-cm steak was removed for Warner- Bratzler shear evaluation. The remaining portion of the meat was vacuum-packaged and stored an additional 14 days. At that time, another 2.54-cm steak was removed for Warner- Bratzler shear evaluation. After cooking, hand cores were taken parallel to the orientation of the majority of the muscle fibers, and another set from the same steak was taken by machine, perpendicular to the steak's cut surface, without regard to muscle fiber orientation. There were no differences (P>.10) in shear force values between steaks from different maturity groups, regardless of coring method. Simple correlation coefficients between coring methods across maturity groups were .81 and .80 (P<.001) for steaks cut 7 and 21 days postmortem, respectively. Spearman rank correlation coefficients for the same data were .84 and .75 (P<.001). Warner-Bratzler shear tests on longissimus muscle cores obtained by either coring method resulted in the same relative data interpretation.
Keywords: Food science; Beef longissimus muscle; Shear force; Coring method